Asymmetric Deformation Induced by Underground Mining: A Case Study of a Mine in Shaanxi, China - Xuesong Zhang; Chenglong Zhang; Zhenhong Li; Yu Li; Yanbo Cao; Ying Zhao; Jiawei Zhou; Kelu He; Xianghui Wang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Geohazards resulting from mining activities must be effectively monitored to mitigate their impact on the environment and human activities. Geohazards such as landslides and collapses caused by open-pit mining are relatively easier to monitor because they are primarily surface based. In contrast, underground mining disrupts the stress balance in the overlying rock layers, leading to complex settlement patterns, including subsidence basins, cracks, and groundwater depletion. This complexity makes monitoring geohazards caused by underground mining particularly challenging, as it depends on subsurface stress conditions and structural conditions. Previous studies have shown that land subsidence caused by horizontal/near-horizontal longwall mining methods is typically symmetrical. However, asymmetry can occur under complex conditions. In this article, asymmetric land subsidence caused by coal mining activities in Shaanxi, China, over the past decade has been investigated using interferometric synthetic aperture radar supplemented by field investigations and geophysical experiments. The results indicate that mining across multiple working faces over the years has led to the formation of a large subsidence funnel above the working faces, with a cumulative subsidence of more than 900 mm in the central area, and has also resulted in the formation of a new subsidence center. Moreover, asymmetric surface deformation has occurred, with both the extent and magnitude of deformation being greater on the southwest side of the working faces than on the northeast side. Through further analysis, we have proposed potential driving mechanisms of asymmetric subsidence, providing valuable insights into the prediction and monitoring of land subsidence due to underground mining.